An inactivating mutation in the vacuolar arginine exporter gene Vae results in culture degeneration in the fungus Metarhizium robertsii. (30th March 2022) - Song, Hui; Bao, Yuting; Zhang, Mingxiang; Liu, Shuxing; Yu, Chaonan; Dai, Jin; Wu, Congcong; Tang, Dan; Fang, Weiguo
Summary: Culture degeneration usually results in great commercial losses in the economically important filamentous fungi, but the genetic causes of the degeneration remain elusive. In the fungus Metarhizium robertsii, we found that deletion of the vacuolar arginine exporter gene Vae caused culture degeneration. Compared to the WT strain, the mutant showed increased apoptosis, reactive oxygen species (ROS) level and mitochondrial membrane potential collapse, reduced conidial yield and abnormal lipid droplet formation. The extent of the degeneration in the mutant gradually increased over the successive subculturing, which eventually became irreversible; compared to the third subculture of the mutant, the seventh subculture showed a lower conidial yield and pathogenicity to insects, stronger apoptosis, higher ROS level and a smaller number of conidial lipid droplets. Incorporation of the genomic clone of Vae could not restore the WT phenotypes in the seventh subculture, but could in the third one. Loss‐of‐function in Vae resulted in vacuolar arginine accumulation and reduction in the cytosolic arginine. This downregulated the expression of the regulator CAG9 of G protein signalling pathway, which accounted for most of the phenotypic changes associated with the degeneration of the mutant. We identified a deleterious mutation that causes culture degeneration in a filamentous fugus.